2015
DOI: 10.1111/caim.12154
|View full text |Cite
|
Sign up to set email alerts
|

Innovating and Exploiting Entrepreneurial Opportunities in Smart Cities: Evidence from Germany

Abstract: Smart City initiatives are considered a vehicle for achieving sustainable development of urban growth. This paper explores the conditions and factors that affect innovation in Smart Cities from an entrepreneurial vantage point. Data was obtained through a series of interviews with German entrepreneurs active in Smart Cities. Beyond examining the importance of a set of factors that originate from the extant literature, our findings suggest that entrepreneurs believe that Smart City initiatives need a clear visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 89 publications
0
31
0
Order By: Relevance
“…This line of research converges with the steadily growing attention to local entrepreneurship as the core engine of viable smart innovation [21,[64][65][66][67][68], because entrepreneurs can (re)build new tailored business models that fit a specific city's needs and conditions. However, a higher-level vision of the city's sustainable future is needed to orient entrepreneurs' efforts, and the government plays an often irreplaceable role in providing this vision, bringing the necessary resources and facilitating the interactions between the relevant actors that are expected to contribute to smart city initiatives [15]. The citizens should be actively involved in these collaborative interactions, because users' appreciation of, and commitment to, urban change is almost always essential to smart initiatives' success [63].…”
Section: The Smart City As An Organizational Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…This line of research converges with the steadily growing attention to local entrepreneurship as the core engine of viable smart innovation [21,[64][65][66][67][68], because entrepreneurs can (re)build new tailored business models that fit a specific city's needs and conditions. However, a higher-level vision of the city's sustainable future is needed to orient entrepreneurs' efforts, and the government plays an often irreplaceable role in providing this vision, bringing the necessary resources and facilitating the interactions between the relevant actors that are expected to contribute to smart city initiatives [15]. The citizens should be actively involved in these collaborative interactions, because users' appreciation of, and commitment to, urban change is almost always essential to smart initiatives' success [63].…”
Section: The Smart City As An Organizational Fieldmentioning
confidence: 99%
“…On the other hand, the smart city idea nurtures a vast global movement, advocated by highly reputed corporations and consulting firms [18]. In addition, smart city initiatives are also strongly encouraged by government funding and/or competitive grants, especially in the European Union, but also in the United States and almost all the most important countries worldwide [15]. Going "smart" is perceived as highly fashionable in the political arena and leaders feel that launching smart initiatives is an important factor to attract investments and talents, especially in the high-tech sectors.…”
Section: The Smart City As An Organizational Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital technologies provide incredible opportunities to citizens in terms of real-time planning, open traffic data, social customer services, etc. At the same time, to effectively create value, these opportunities must meet the needs of emerging lifestyles (Kraus, Richter, Papagiannidis, & Durst, 2015;Verganti, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They find evidence for such differences and argue that science communication needs to be improved to align expectations. Richter, Papagiannidis, Kraus and Durst (2015) position their paper at the regional level of analysis when they ask which characteristics of smart cities impact on the activities of technology entrepreneurs. They position their paper in the knowledge spillover and social capital theories when they suggested that the Smart City would be a favourable location for entrepreneurs.…”
Section: Introduction To the Special Issuementioning
confidence: 99%